The Influence of the Realistic Mathematics Education (RME) Approach and Students' Creativity on Mathematical Problem-solving Ability - Arief Hidayat (Proceeding International Conference on Mathematics and Learning Research, 2025)
This study aims to determine the effect of RME (Realistic Mathematics Education) learning and student creativity on mathematical problem-solving abilities in the topic of systems of linear equations in two variables (SPLDV). This research uses a quantitative approach with a sample of 46 eighth-grade junior high school students. The research method is quantitative with a nonequivalent control group design, consisting of two groups: an experimental group and a control group. The sampling technique used is purposive sampling. The research instruments include essay-type tests and questionnaires, while the data analysis uses two-way ANOVA. The research results lead to the following conclusions: 1) There is an effect of the RME learning model on mathematical problem-solving ability., 2) Student creativity influences mathematical problem-solving ability, 3) There is no significant interaction between the RME learning model and student creativity on mathematical problem-solving ability.